Bevacizumab Injection in Patients with Age-Related Macular Degeneration Associated with Poor Initial Visual Acuity - Leila El Matri; Rym Bouraoui; Ahmed Chebil; Fedra Kort; Mejda Bouladi; Rym Limaiem; Hana Landoulsi (Journal of Ophthalmology)
Purpose. To evaluate functional and anatomic effects of intravitreal bevacizumab in patients with neovascular AMD and initial low visual acuity. Methods. Retrospective case series of 38 eyes with neovascular AMD and initial visual acuity of 20/200 or less, treated with intravitreal bevacizumab injection. Results. Mean followup was 14.1 months ±7.1 (range: 5 to 24 months). Mean logMAR vision at baseline was 1.38 logMAR ±0.33, at 6 months was 1.14 logMAR ±0.37 (𝑃=0.001) and at 12 months was 1.22 logMar ±0.33 (𝑃=0.004). Mean baseline central retinal thickness was 431 μm ±159.7 at 6 months was 293.43 μm  ±122.79 (𝑃=10−4) and at 12 months was 293.1 μm  ±130 (𝑃=0.004). Visual acuity improved in both patients with or without prior PDT treatment. Conclusions. Intravitreal bevacizumab injection may increase the chance of visual acuity gain in neovascular AMD even in cases with initial low visual acuity.